Liquid–liquid crystalline phase separation in biomolecular solutions. (December 2021) - Fraccia, Tommaso P.; Zanchetta, Giuliano
Abstract: Liquid–liquid phase separation (LLPS) and liquid crystalline (LC) ordering are ubiquitous phenomena in nature, in a variety of biomolecular solutions. Here, we review instances in DNA, nanocellulose, and other systems, where they occur together, leading to the formation of liquid–liquid crystalline phase separation (LLCPS), and we highlight analogies, differences, recent advances, and open questions. Remarkably, the intrinsic fluid yet ordered nature of LC, combined with the spatial confinement induced by LLPS, leads to peculiar biomolecular compartments suitable for a broad range of applications, ranging from material science to synthetic biology. We argue that tools from the LC field help to address still unexplained processes such as the onset of phase transitions in intracellular biomolecular condensates. Graphical abstract: Image 1